Case report: Recurrent nocturnal awakenings in cluster headache: a different type of ghost attack - Giuliani, Giada; Gorgoni, Maurizio; Altieri, Marta; Di Piero, Vittorio (Frontiers in Neurology, 2023)
Introduction Cluster headache (CH) is a trigeminal autonomic cephalalgia characterized by attacks of severe unilateral pain associated with ipsilateral autonomic symptoms. Cluster headache attacks exhibit nocturnal predilection, and sleep disorders could be the first manifestation of an incipient cluster period. Sleep alterations in cluster headache patients may reflect the pivotal role of the hypothalamus, which is crucially involved in the pathophysiology of this primary headache. We describe the case of a patient affected by episodic cluster headache who experienced a sleep disorder after starting therapy with verapamil. Case presentation A 47-year-old man was affected by episodic cluster headache, characterized by attacks of excruciating pain in the left orbital and temporal regions, associated with prominent ipsilateral vegetative symptoms. Headaches occurred during the night, with one or two nocturnal attacks appearing at 11.30–12 p.m. and 4–4.30 a.m. Preventive treatment with verapamil was started, with immediate pain relief. Later, he experienced consecutive nocturnal awakenings for a couple of weeks, always at the same time, without any pain or autonomic symptoms. He was not agitated and did not need to get out of bed; after the awakenings, he reported sleep disturbances with vivid dreams. Discussion and conclusion This case represents the first description of recurrent cyclic nocturnal awakenings, without pain and autonomic symptoms, in a patient with episodic cluster headache during the active phase of a cluster bout. Nocturnal awakenings, started after the introduction of effective preventive therapy, might be an unusual form of “ghost attacks.” After the beginning of prophylactic therapy, patients often describe mild pain or localized pressure in the same localization of CH attack. Similarly, the appearance of sleep disturbances, without any pain or vegetative symptoms, should be regarded as a warning sign of a still active cluster bout. Since these manifestations may influence therapeutic management, they should be carefully investigated.